A thermogelling organic-inorganic hybrid hydrogel with excellent printability, shape fidelity and cytocompatibility for 3D bioprinting. (1st April 2022) - Hu, Chen; Ahmad, Taufiq; Haider, Malik Salman; Hahn, Lukas; Stahlhut, Philipp; Groll, Jürgen; Luxenhofer, Robert
Abstract: Alginates are the most commonly used bioink in biofabrication, but their rheological profiles make it very challenging to perform real 3D printing. In this study, an advanced hybrid hydrogel ink was developed, a mixture of thermogelling diblock copolymer, alginate and clay i.e. Laponite XLG. The reversible thermogelling and shear thinning properties of the diblock copolymer in the ink system improves handling and 3D printability significantly. Various three-dimensional constructs, including suspended filaments, were printed successfully with high shape fidelity and excellent stackability. Subsequent ionic crosslinking of alginate fixates the printed scaffolds, while the diblock copolymer is washed out of the structure, acting as a fugitive material/porogen on the (macro)molecular level. Finally, cell-laden printing and culture over 21 d demonstrated good cytocompatibility and feasibility of the novel hybrid hydrogels for 3D bioprinting. We believe that the developed approach could be interesting for a wide range of bioprinting applications including tissue engineering and drug screening, potentially enabling also other biological bioinks such as collagen, hyaluronic acid, decellularized extracellular matrices or cellulose based bioinks.